Differential Regulation of P27Kip1 Expression by Mitogenic and Hypertrophic Factors - Marc J. Servant; Philippe Coulombe; Benjamin Turgeon; Sylvain Meloche (2000)
Platelet-derived growth factor-BB (PDGF-BB) acts as a full mitogen for cultured aortic smooth muscle cells (SMC), promoting DNA synthesis and cell proliferation. In contrast, angiotensin II (Ang II) induces cellular hypertrophy as a result of increased protein synthesis, but is unable to drive cells into S phase. In an effort to understand the molecular basis for this differential growth response, we have examined the downstream effects of PDGF-BB and Ang II on regulators of the cell cycle machinery in rat aortic SMC. Both PDGF-BB and Ang II were found to stimulate the accumulation of G1 cyclins with similar kinetics. In addition, little difference was observed in the expression level of their catalytic partners, Cdk4 and Cdk2. However, while both factors increased the enzymatic activity of Cdk4, only PDGF-BB stimulated Cdk2 activity in late G1 phase. The lack of activation of Cdk2 in Ang II-treated cells was causally related to the failure of Ang II to stimulate phosphorylation of the enzyme on threonine and to downregulate p27Kip1 expression. By contrast, exposure to PDGF-BB resulted in a progressive and dramatic reduction in the level of p27Kip1 protein. The time course of p27Kip1 decline was correlated with a reduced rate of synthesis and an increased rate of degradation of the protein. Importantly, the repression of p27Kip1 synthesis by PDGF-BB was associated with a marked attenuation of Kip1 gene transcription and a corresponding decrease in Kip1 mRNA accumulation. We also show that the failure of Ang II to promote S phase entry is not related to the autocrine production of transforming growth factor-β1 by aortic SMC. These results identify p27Kip1 as an important regulator of the phenotypic response of vascular SMC to mitogenic and hypertrophic stimuli.